2014
DOI: 10.1017/s2045796014000018
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective and prospectively assessed childhood adversity in association with major depression, alcohol consumption and painful conditions

Abstract: These findings help to allay concerns that associations between childhood adversities and health outcomes during adulthood are merely artefacts of recall bias. In this study, retrospective and prospective assessment strategies produced similar results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 21 publications
4
50
0
Order By: Relevance
“…reported an increased risk of poor self‐rated health on the order of d = .44 where we report d = .49. Second, consistent with observations from previous analyses of the agreement between prospective and retrospective measures of specific childhood adversities (Hardt & Rutter, ; Patten et al., ), we found that prospective and retrospective ACE measures in the Dunedin cohort agreed only modestly. Such modest agreement may raise eyebrows, but it should be interpreted in context.…”
Section: Discussionsupporting
confidence: 90%
“…reported an increased risk of poor self‐rated health on the order of d = .44 where we report d = .49. Second, consistent with observations from previous analyses of the agreement between prospective and retrospective measures of specific childhood adversities (Hardt & Rutter, ; Patten et al., ), we found that prospective and retrospective ACE measures in the Dunedin cohort agreed only modestly. Such modest agreement may raise eyebrows, but it should be interpreted in context.…”
Section: Discussionsupporting
confidence: 90%
“…This study relies on prior estimates of ACEs association with disease, healthcare expenses, and DALYs which have their own underlying limitations. The ACEs-associated fraction estimates are based on our prior study [13,24] using retrospective ACEs data which are selfreported and subject to recall bias [67,68]. Total associations with 4+ ACEs in our prior study are generally consistent with prior BRFSS studies for asthma and depression (e.g.…”
Section: Limitationssupporting
confidence: 65%
“…Moreover, some other reports have suggested that subjects under-report childhood physical maltreatment when it is measured retrospectively [82,83]. Recent studies that compared associations of retrospective and prospective assessments of childhood physical maltreatment and health have shown that the associations remained in the same direction; however, the associations between retrospective childhood physical maltreatment and self-reported outcomes were over-estimated [74,84]. Accordingly, since the measurement of internalizing symptoms in this study was self-reported, it is plausible that the total effects and direct effects presented here are over-estimated, while the indirect effects may be under-estimated.…”
Section: Discussionmentioning
confidence: 99%